Analisis Pengaruh Selfie Marketing Value Co-Creation, Kepuasan Pelanggan Terhadap Peningkatan Brand Image - Natasya br Hutapea; Mariana Simanjuntak (Pusat Riset dan Inovasi Nasional, 2024)
Brand image is very important to increase sales of micro, small, and medium enterprises (MSMEs). By satisfying consumers, companies will make them loyal to the product. A deep understanding of the market and its behavior will facilitate efforts to satisfy consumers, because marketers will have insight into consumer buying interest in a product and their perception of the company's products compared to competitors' products. In addition, marketers want customers to be loyal to the company's products, so they will also try to understand other factors that influence the decision to buy or repurchase. The problem at UD. Parna Ulos, sales are decreasing. To handle this problem, this study aims to examine how the variables of selfie marketing (X1), Value co-creation (X2), Customer satisfaction (Z), and increasing brand image (Y) influence each other. This study uses questionnaires and interviews as tools to collect data, and uses the Structural Equation Modeling (SEM) data processing method with the Partial Least Square (PLS) approach and the assistance of Statistical and Service Solution (SPSS) software. This study is expected to produce a structural model and be able to identify the influence on the proposed hypothesis.